Successional cocoa agroforests of the Amazon-Orinoco-Guiana shield - Somarriba, Eduardo; Lachenaud, Philippe (2015)
Cocoa was used as a fruit in its native range. Cocoa fruits were harvested from “wild” cocoa stands embedded into the forests growing on the high terraces of the Amazon and Orinoco river systems and in the Guiana shield. “Wild” cocoa stands resulting from human intervention and disturbance of the local forest ecosystem are called subspontaneous cocoa stands. We propose that these sub-spontaneous cocoa forests are a new type of cocoa production system that we propose to call “successional cocoa agroforest.” This article (1) describes the history of extractive cocoa in the Amazon basin, (2) outlines the possible historic path of domestication and use of cocoa subspontaneous stands, (3) specifies the biophysical and cultural processes that determine the creation–destruction–regeneration of the successional cocoa agroforest, (4) proposes a model for the functioning of this cocoa production system, and (5) documents the scarce information available on the changes in both the forest vegetation and biomass, and cocoa population numbers along the course of forest succession. This study shows the need to broaden the popular five classes classification of coffee and cocoa production systems (open sun cultivation, specialized shade, commercial shade, mixed shade, and rustic systems) to include a sixth type, the “successional cocoa agroforest.”